Organizational Innovation in Public Services
X, 283 p.
Keywords: In the wake of the economic crisis, many public services are facing a challenging environment in which they receive less funding but are expected to deliver better services. Organisational Innovation in Public Services develops new theoretical models and analyses case studies to provide an important insight into how to modernise public services.